Doom patrol. The complete second season [videorecording (Blu-Ray)] - Carver, Jeremy (Warner Bros. Home Entertainment, 2021)
Following the mysterious disappearance of The Chief, these reluctant heroes will find themselves in a place they never expected to be, called to action by none other than Cyborg, who comes to them with a mission hard to refuse. Part support group, part Super Hero team, the Doom Patrol is a band of superpowered freaks who fight for a world that wants nothing to do with them.